Caracterización físico- química de los principales humedales de Jalca de la Concesión para Conservación Alto Huayabamba. 2012 - Navarro Cahuaza, Alexis (2012)
The High Conservation Concession Huayabamba, its extension covers two ecoregions such as the Jalca and Yunga that is located in the headwaters of the right bank Huayabamba, major tributary of the Huallaga in the San Martín region is in this conservation area which hosted research work entitled "Physico-chemical characterization of the major wetlands Jalca of High Conservation Concession Huayabamba.2012", this study aimed to identify the main wetlands Jalca of SCF, determine the chemical (Oxygen dissolved ammonium and nitrate) of major wetlands of Jalca, determine the physical characteristics (pH, temperature, electrical conductivity) of major wetlands of Jalca and evaluate the results to define the application of wetlands Jalca of CCAH to the Convention Ramsar. The study area was the ecoregion Jalca in wetlands that exist in this area (lakes, rivers and bogs or wetlands) In the present research work was carried out at two different times during the rainy season (March and April) and dry season (June and July) was characterized by a total of 28 wetlands in four (04) sectors such as: Huayabamba, Yonán, Quinguyacu and Yampió in these sectors was fifty-two (52) samples, 11 samples in Huayabamba, 13 Yonán samples, 12 samples and 16 samples Yampió Quinguyacu, basic parameters analyzed were temperature, dissolved oxygen, potential of hydrogen, ammonium, nitrate and electrical conductivity. From the study it appears that the chemical parameters are suffering alteration NH4, pH and overall average of rivers, there are many factors affecting the pH as is excessive absorption of ions on cation constants also allow the increase rains it. With respect to the concentration of ammonium is caused by metabolic processes such as agriculture, livestock farming which is the case here, that increases your concentration level. The overall averages of the chemical characteristics obtained during the two periods were: In lakes have dissolved oxygen with 6.53 mg / lt, at pH 8.34 mg / lt, in NH4 with 0.008 mg / lt and NO3 with 0.025 mg / lt. In rivers have dissolved oxygen with 7.18 mg / lt, at pH 8.76 mg / lt, in NH4 with 0.02 mg / lt and NO3 with 0.06 mg / lt. In peatlands have dissolved oxygen with 5.63 mg / lt, at pH 8.39 mg / lt, NH4 with 0.54 mg / lt and 1.88 mg NO3 with mg/ lt. The overall averages of the physical characteristics obtained during the two periods were: In gaps we 11.33 ° C temperature and CE 102.55 us / cm. In rivers we temperature 11.28 ° C and 107.22 CE us / cm. In peatlands have in temperature with 13.4 ° C, and CE 129.21 us / cm. We note that wetlands have undergone studies have been characterized at different times that are rainy and dry, met to apply for the International Ramsar Convention because they show physicochemical characteristics for conservation of aquatic environments, and the types these wetlands are: M, O, Tp, U, Xp established the Ramsar Convention, see table No. 01 description.